SOCIAL ENGINEERING: CRISIS IN HUMANITY - Kevin Tjendrawinata (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Digital development in Indonesia have had a significant impact and contribution, both positive and negative. When misused, various kinds of crimes in the cyber world (cybercrime) begin to emerge, one of which is Social Engineering techniques. Using previous studies as references, it can be concluded that Social Engineering is a technique of attacking through social mechanisms or human interaction (persuasions, influences, and other interactions), aiming to control the actions of victims, both consciously and unconsciously. Due to the nature of the Social Engineering case is user negligence, not all companies have compensation policy for losses. On the other hand, users/consumers feel aggrieved due to the